Evaluation of the Effectiveness of Agricultural Shows in Oyo and Ondo States of Nigeria - Jibowo, A. A. (Faculty of Agriculture, University of Ife, 2015)
The purpose of the study was to evaluate the effectiveness of agricultural shows in Oyo and Ondo States. Data were obtained from 75 farmers who had participated in agricultural shows before, and 98 who had not, between September and November 1981, through interviews. Findings revealed that agricultural shows were effective in terms of imparting knowledge to the participants in the major areas of agriculture namely, crop, animal, fishery, and forestry management, but application of such knowledge was most frequent in crop management. The University of Ife had not been effective in attracting many participants to its booths, although it had been effective in passing knowledge of its exhibits to those who visited its booths, and such knowledge had been largely applied, except of Ife Brown cowpeas, the cultivation of which needed to be encouraged among the participants.